THE PARAMETERS OF THE OXYGEN STATUS IN THE ASSESSMENT OF PROGNOSIS OF A HEMODYNAMICALLY SIGNIFICANT PATENT DUCTUS ARTERIOSUS PRETERM NEONATAL INFANTS - M. V. Perestoronina; O. V. Korpacheva; S. V. Palyanov; V. T. Dolgikh (Общая реаниматология)
Objective: to estimate the significance of capillary blood oxygen parameters for the prognosis of longstanding hemodynamically significant patent ductus arteriosus (HSPDA) in extremely low birthweight (ELBW) neonates. Subjects and methods. On day 8 of their life, two groups of ELBW newborn infants with and without HSPDA were examined for capillary blood рН, рkО2, %SO2с, O2ct, АkDO2, and RIk, as well as mechanical ventilation (MV) parameters (Pip, MAP, and FiO2). Comparison of two independent samples used nonparametric statistical tests: MannWhitney test, Wald Wolfowitz test, and Kolmogorov-Smirnov test. A logistic regression analysis was used to assess the relationship between the examined parameters and the presence or absence of HSPDA. ROC curves were constructed, by choosing the cut-off point, to estimate the predictive power of the model developed using logistic regression. Results. The developed model has high sensitivity and high specificity (84,6 and 97% respectively). The logistic regression equation takes the form: -0.479•О2сt+0.708•Pip-6.823. Conclusion. Capillary blood oxygen parameters proved suitable for predicting the duration of HSPDA functioning. The resultant good predictive power of the model developed for day 8 of life points to the fact that this period is critical from the viewpoint of resolution of respiratory distress syndrome or development of bronchopulmonary dysplasia, which is crucially significant for MV duration and further prediction. HSPDA is one of the most important factors contributing to the development of bronchopulmonary dysplasia in ELBW neonatal infants.